LncRNA-T199678 Mitigates α-Synuclein-Induced Dopaminergic Neuron Injury via miR-101-3p - Bu, Lu-Lu; Xie, Ying-Yu; Lin, Dan-Yu; Chen, Ying; Jing, Xiu-Na; Liang, Yan-Ran; Peng, Su-Dan; Huang, Kai-Xun; Tao, En-Xiang (Frontiers in Aging Neuroscience, 2020)
Parkinson's disease (PD) is the second most common neurodegenerative disorder characterized by dopaminergic neuron death and the abnormal accumulation and aggregation of α-synuclein (α-Syn) in the substantia nigra (SN). Although the abnormal accumulation of α-Syn can solely promote and accelerate the progress of PD, the underlying molecular mechanisms remain unknown. Mounting evidence confirms that the abnormal expression of long non-coding RNA (lncRNA) plays an important role in PD. Our previous study found that exogenous α-Syn induced the downregulation of lncRNA-T199678 in SH-SY5Y cells via a gene microarray analysis. This finding suggested that lncRNA-T199678 might have a potential pathological role in the pathogenesis of PD. This study aimed to explore the influence of lncRNA-T199678 on α-Syn-induced dopaminergic neuron injury. Overexpression of lncRNA-T199678 ameliorated the neuron injury induced by α-Syn via regulating oxidative stress, cell cycle, and apoptosis. Studies indicate lncRNAs could regulate posttranscriptional gene expression via regulating the downstream microRNA (miRNA). To discover the downstream molecular target of lncRNA-T199678, the following experiment found out that miR-101-3p was a potential target for lncRNA-T199678. Further study showed that the upregulation of lncRNA-T199678 reduced α-Syn-induced neuronal damage through miR-101-3p in SH-SY5Y cells and lncRNA-T199678 was responsible for the α-Syn-induced intracellular oxidative stress, dysfunction of the cell cycle, and apoptosis. All in all, lncRNA-T199678 mitigated the α-Syn-induced dopaminergic neuron injury via targeting miR-101-3p, which contributed to promote PD. Our results highlighted the role of lncRNA-T199678 in mitigating dopaminergic neuron injury in PD and revealed a new molecular target for PD.